The role of visioning in business network strategizing - Abrahamsen Morten H.; Halinen Aino; Naudé Peter (Elsevier (Commercial Publisher), 2025)
Visioning the future is an essential aspect of strategizing. However, how managers make sense of their networked business environment, future changes in it, and how this visioning informs their interaction and networking has hardly been explored. Drawing on organizational foresight and business network research, we enhance the visioning concept by conducting an abductive qualitative case study on its role in business network strategizing. By comparing forward-looking and backward-looking perspectives of managers in companies within a particular business network, the study reveals what managers can foresee, what limits their visioning, and to what extent visioning informs network strategizing. Our findings suggest that visioning helps managers to openly contemplate the future, to envisage structural changes, detect probable trends, and form strategic intentions, but individual cognitive frameworks and network constraints limit their visioning. The study contributes to the current sensemaking view of network strategizing by proposing a conceptual model where visioning forms an important step in between reflection and networking, and by showing how managers consciously prepare for the future.